"In Great Degree of Spirit": Higher Education Studies at the University of Toledo (Studying the History of Higher Education Journal, 2024)
The University of Toledo’s Higher Education program and its Russel Center for the Study of Higher Education host the SHHE Journal. This first article provides a historical account of their origins and growth. The beginnings of higher education studies at the University of Toledo marks a significant milestone in the institution’s history. Introduced in 1960 at the doctoral level, the Higher Education program was amongst the pioneers of doctoral education at the municipal Toledo University. Its faculty awarded some of the first doctoral degrees at the university and established the first interdisciplinary research center on higher education studies in the state of Ohio. Drawing on archival resources and secondary research, this article examines the broader context of doctoral education in the United States and Ohio, the visionary leadership of the education faculty who championed the cause of graduate education, and the expansion of the program through its own department and research center. Despite many challenges, the Higher Education program and its research center thrived and evolved over the decades. Today, the program boasts more than 650 graduates while its alumni serve institutions of higher education nationwide.
Keywords: higher education program; doctoral degrees; The University of Toledo; state of Ohio; center for the study of higher education